Penentuan hubungan laju-aliran lalu lintas jalan arteri - Ahmad Raqib Ab. Ghani,; Wan Hashim Wan Ibrahim,; Ahmad Farhan Mohd Sadullah, (2006)
Presently, there is no published relationship between speed and traffic flow for arterial road in Malaysia. Report on Traffic Study Malaysia indicates the relationships of speed and traffic flows for uninterrupted flow facilities. An arterial road is a road consisting of traffic light junctions within 3 km distance or less and carrying high through traffic volume. This study is conducted towards producing the relationships between speed and traffic flow for arterial roads in Malaysia. The speed-flow relationships was developed using an existing traffic flow model. The specific aim of this study is to determine which model is appropriate with respect to Malaysian traffic characteristics. The relationships of speed and traffic flow are two parameters that are very important for planning and modeling of transportation facilities. In this study, travel speed and traffic flow were collected at several selected sites. The collected data were analyzed based on Greenshields, Greenberg, Underwood and Drake Models. The results of the analysis study has shown that Underwood Model is the most suitable model that can be used to define the relationships between speed and traffic flow based on Malaysian road condition. The data of observed free-flow speed in the field were also compared with predicted free-flow speed by each model